Kemampuan Menggunakan Adjektiva Pada Anak Usia 10 Tahun : Kajian Psikolinguistik - Khuzaifah, Syaniba; Putra, Dona Aji Karunia (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Language is a tool that is certainly familiar to use in society, because without language we will not be able to communicate with other people around us. Therefore, with language, of course, we can more easily socialize with the people around us. This study aims to describe the forms, functions, and types of adjectives semantically mastered by a ten-year-old child with the initials Zhl. The method used in this research activity is a qualitative descriptive method, which is accompanied by a note-taking technique by listening and then recording language skills in the study of adjective syntax. The subjects in this study were ten year old children with the initials Zhl. The object of this research is a ten year old child who is playing with his friends. The results showed that the adjectives used were attributive adjectives, predicative adjectives, and inverse predicative adjectives. The function of adjectives in speech is as a complement or explanation of a sentence, and as a predicate in a sentence.